2000
DOI: 10.1002/(sici)1098-2736(200001)37:1<3::aid-tea2>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

From Corrector to Collaborator: The Range of Instructor Roles in Writing-Based Natural and Applied Science Classes

Abstract: This study of writing-intensive (WI) undergraduate natural and applied science courses examined the relationships among instructors' course goals, instructional activities, and students' assessment of their learning of content and writing. Using multiple sources of data, investigators found that instructors held common goals but varied greatly in their instructional activities. Findings suggest that science instructors can be described along a continuum anchored by instructor as corrector on one end and instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 20 publications
3
12
0
2
Order By: Relevance
“…The students' comments also confirm other research findings (Chinn & Hilgers, 2000;Keys, 1999;Kelly & Chen, 1999;Prain & Hand, 1996) that claim certain aspects of task design and particular classroom conditions are likely to promote learning through writing. The writing tasks should entail meaningful audiences for whom student writers recognize task demands and have strategies to address these demands.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The students' comments also confirm other research findings (Chinn & Hilgers, 2000;Keys, 1999;Kelly & Chen, 1999;Prain & Hand, 1996) that claim certain aspects of task design and particular classroom conditions are likely to promote learning through writing. The writing tasks should entail meaningful audiences for whom student writers recognize task demands and have strategies to address these demands.…”
Section: Discussionsupporting
confidence: 77%
“…As their responses indicated, students perceived that this task required them to clarify concepts for themselves to explain them to others, and that this process focused and enhanced their learning. The students' comments also confirm Chinn and Hilgers' (2000) claim that students learn from writing when there are frequent verbal and written interaction between student and teacher, participation in a collaborative learning community, clear guidelines for writing, and opportunities to write for other audiences. In other words, as noted by Lave and Wenger (1991), classroom conditions serve learning when there is a range of meaningful communicative practices that support students in all stages of writing, including feedback on their initial and advanced efforts.…”
Section: Discussionmentioning
confidence: 57%
“…University and college level activity appears to have been stimulated by two independent factorsinstitutional requirements about writing-intensive courses directed at the quality of written communications for graduation, and the perceived power of writing in service of science learning. Chinn and Hilgers (2000) found that professors who assumed the role of collaborator rather than strictly the role of evaluator produced better quality student writing and student attitudes toward science writing and the science course. .…”
Section: Current Trends In Writing-to-learn Sciencementioning
confidence: 94%
“…Writing-to-learn emphasizes the powerful role of language in the production and presentation of knowledge (Connolly, 1989), and shows that the symbol systems typically used in communication play a critical role in the construction of meaning. Using writing-to-learn techniques in the science classroom is considered a tool for improving thinking and communication skills (Keys, 2000), facilitating enculturation into the community of science practitioners (Rowell, 1997;Chinn & Hilgers, 2000), enabling students to discover knowledge (Connolly 1989), developing an understanding of science (Rivard, 1994;Keys et al, 1999;Rivard & Straw, 2000) and engendering scientific literacy (Wellington & Osborne, 2001).…”
Section: Introductionmentioning
confidence: 99%